2007
DOI: 10.1002/pmic.200600526
|View full text |Cite
|
Sign up to set email alerts
|

Phanerochaete chrysosporium soluble proteome as a prelude for the analysis of heavy metal stress response

Abstract: A 2-D reference map in pI range 3-10 was constructed for the soluble protein fraction of Phanerochaete chrysosporium growing vegetatively under standard conditions. Functional annotation could be made for 517 spots out of 720 that were subjected to MALDI-TOF-MS analysis, according to the specific accession numbers from the P. chrysosporium genomic database. Further analysis of the data revealed 314 distinct ORFs, 118 of which yielded multiple spots on the master gel. Functional classification of the proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 80 publications
2
20
0
1
Order By: Relevance
“…This enzyme participates in the lignin biosynthesis pathway (36). Moreover, a 9-fold-elevated level of cinnamoyl-CoA reductase protein in P. chrysosporium under Cu stress suggests a role of this enzyme in stress response (37). In addition to the genes reported in Table 1, 73 genes exhibiting no homology in the databases are upregulated more than 10-fold.…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 99%
“…This enzyme participates in the lignin biosynthesis pathway (36). Moreover, a 9-fold-elevated level of cinnamoyl-CoA reductase protein in P. chrysosporium under Cu stress suggests a role of this enzyme in stress response (37). In addition to the genes reported in Table 1, 73 genes exhibiting no homology in the databases are upregulated more than 10-fold.…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 99%
“…Now that the genome of Phanerochaete chrysosporium has been sequenced and annotated (20, 34), proteomic work has begun on this intensively researched white rot fungus. Recent studies have shown variation in the expression patterns of many extracellular and cytoplasmic enzymes relevant to ligninolysis (1,21,26,28,30,35) but have so far revealed little about the regulation of membrane-associated components. In part, this lack of information likely reflects the poor behavior of some membrane proteins during the electrophoretic separations that are generally employed (27).…”
mentioning
confidence: 99%
“…The supernatant was concentrated 100-fold by an Amicon 10 kDa filter at 4°C. Then TCA-acetone method was used to extract the total extracellular proteins (Ozcan et al 2007). A volume of 5 ml 10% TCA in acetone containing 0.07% b-mercaptoethanol was added and vortexed, then incubated at -20°C for 45 min and centrifuged at 15,0009g for 15 min.…”
Section: Measurement Of Proteomementioning
confidence: 99%